A A Holistic Inclusive Education Approach to Character Development of Students with Special Needs - Dika Putri, Neysa; Wakhudin, Wakhudin (Jurnal Prima Edukasia, 2026)
Everyone has the right to education, including children with special needs. Education aims to shape character, develop thinking skills, and foster empathy. The purpose of this study is to analyze the development of independence and perseverance in students with special needs through a holistic, inclusive education approach and to identify supporting and inhibiting factors. This study employed a qualitative descriptive approach with a case study method. The research was conducted at Kalitapen 1 Elementary School, located in Purwojati District, Banyumas Regency, selected based on specific criteria and local wisdom as a representative case reflecting the dynamics of inclusive education in the region. The research participants included classroom teachers, students with hearing and speech impairments, students with learning disabilities, and parents. The object of the study was the educational ecosystem involved in implementing the holistic inclusive approach. Qualitative data were collected through observations and interviews. Data were analyzed using qualitative procedures, including data collection, reduction, and interpretation. The findings indicated that the holistic development of independence and perseverance among deaf students and slow learners was fostered through the synergy of prompt-based instructional methods, family partnerships, and the strengthening of self-awareness. Holistic, context- based character education was found to function as a transformative process that internalizes values into daily habits, making it particularly relevant and effective for students with special needs.